What about the non-legal facts: Revising Allen and Pardo's analytical distinction between law and fact. (October 2019) - Sevelin, Ellika
This paper deals with the distinction between law and fact. In the article 'The myth of the law-fact distinction' (Allen and Pardo, 2003a), Ronald Allen and Michael Pardo argue that there is no ontological, epistemological or analytical distinction between law and fact. Instead, they claim that the distinction ought to be understood pragmatically, by considering whether the judge or jury is in the best position to decide the question. The problem with this is that it does not add to the understanding. In a soon-forgotten passus they suggest that the distinction is between legal and non-legal facts, rather than between law and fact. In this paper I revise the article by Ron and Pardo and make an argument in favour of the distinction between legal and non-legal facts. The notion of 'legal' and 'non-legal' underlines the fact that the dichotomy is relevant specifically from a legal point of view. In the legal context different consequences apply to law and fact, the same is not true in a non-legal context.